ESPORTS BUSINESS MANAGEMENT - David P. Hedlund, Gil B. Fried, Ronald "Rick" Smith (Human Kinetics, Inc., 2021)
"This book addresses the current issues and challenges facing existing stakeholders in esports, how the industry will evolve in the coming years, and the multifaceted and diverse nature of the business and management of esports from multiple international perspectives. This book is intended to prepare and educate those wishing to better understand the digital world of esports, not to mention those that also strive to work in the industry"